A Practical Approach to Spectrum Analyzing Unit Using RTL-SDR - Rahman, Md. Habibur; Islam, Md. Mamunoor (Rajshahi University Journal of Science and Engineering, 2016)
In the present scenario, there has been an immense advancement in the field of wireless communication in this modern engineering world. Now-a-days Software Defined Radio (SDR) technology is an indisputable emerging technology and presents new challenges for communications engineers. The advancement of SDR system has made significant progress in recent years which makes it as a serious substitute of traditional hardware radio architectures where the mathematical procedures are obligatory to decode and process radio signals using analogue circuitry. Recently, computers have turned out to be powerful enough to do the required mathematical calculations using software. So aim of this paper is to demonstrate a RTL-SDR based spectrum analyzer which can be used proficiently as an alternative of existing hardware spectrum analyzer. This approach will lessen the complexity of analogue hardware system with the higher tractability of software based filtering and demodulation techniques. As RTL-SDR devices are quite cheap (Approximately 20) and small sized, this system also offers cost effectiveness with provision of portability. An experimental study was conducted with suitable conditions to examine the feasibility and efficiency of the proposed system. The outcome of experimental result is thoroughly examined in this paper.